Creative Reindustrialisation of the Second-Tier Cities in the Digital Transformation Era: A Study Using SciVal Tools - Turgel, Irina D.; Antonova , Irina S. (Economy of Regions, 2023)
Nowadays, creative industries are becoming a driving force for urban economic development, inspiring the emergence of a new conceptual framework in regional economy, which includes the notion of «creative reindustrialisation of cities». Traditionally, scientific review is used to present theoretical and methodological foundations of a new subject area. However, individual use of such tools as author search or information systems analysis does not allow for a comprehensive scientific review on the emerging topic. The study aims to substantiate the creation of a new subject area, focused on the creative reindustrialisation of the second-tier cities in the digital transformation era, and to identify theoretical and practical trends in its development. To this end, the following steps were performed: identifying specific elements and establishing a general model of the subject area; comparing model and existing elements; modelling the new subject area using the developed logical scheme; analysing the new subject area and comparing it with existing ones. Since the examined subject area is not presented in the SciVal system, this paper developed the logical scheme for creating a new subject area through keywords, and proposed four models. After the models were tested using the SciVal tools, the subject area of regional economics called Creindustrialisation was established. It identified a pool of the most relevant publications on regional economy, confirming the importance of the creative reindustrialisation of cities, including second-tier cities, and assessing the impact of the digital context on cultural transformations. It was revealed that digitalisation of creative industries leads to the convergence of social classes. However, mindless replication of creative practices at the local level reduces their efficiency, hindering the widespread of the creative reindustrialisation tools, requiring further research.